Hypertension-induced cognitive impairment: insights from prolonged angiotensin II infusion in mice. Issue 10 (October 2018) - Foulquier, Sébastien; Namsolleck, Pawel; Hagen, Britt; Milanova, Irina; Post, Mark; Blankesteijn, W.; Rutten, Bart; Prickaerts, Jos; Oostenbrugge, Robert; Unger, Thomas
Abstract The causal relation between hypertension and cerebral small vessel disease (cSVD) remains elusive, and appropriate animal models are scarce. We aimed to assess the relevance of prolonged angiotensin II-induced hypertension in mice for the study of cSVD. Adult male C57BL/6 mice were continuously infused for 3 months with Angiotensin II (Ang II; 2 µg/kg/min, sc) or saline (control) via osmotic minipumps. Blood pressure, neurological function, locomotor activity, and working memory (Y-maze alternation task) were assessed throughout the study. Short-term memory performance (object location task) was measured after 3 months of infusion. Blood–brain barrier (BBB) function was assessed by the presence of IgG leakage and quantified in each brain area of interest. Microglial activation and myelin loss were studied in the areas of leakage. Systolic blood pressure increased and remained elevated over the 3 months of Ang II infusion, while neurological scores and locomotor activity did not change. Working memory performance was also not changed, yet short-term memory performance was impaired in Ang II-treated mice compared to controls. While BBB leakages were present in both groups, mainly in the neocortex, hippocampus, and cerebral nuclei, Ang II-treated mice showed greater leakage than control mice, along with greater microglial density and soma size. Myelin loss was observed for the largest leaks. Prolonged Ang II-induced hypertension is associated with large BBB leaks, microglial activation, myelin loss, and memory dysfunction in the absence of stroke.